2017
DOI: 10.1093/jrr/rrx003
|View full text |Cite
|
Sign up to set email alerts
|

Combined modality therapy in Stage IIIA non–small cell lung cancer: clarity or confusion despite the highest level of evidence?

Abstract: Recent years have witnessed a number of clinical trials in Stage IIIA non–small cell lung cancer (NSCLC) comparing (A) induction chemotherapy (CHT) with induction CHT and radiotherapy (RT), each followed by surgery; (B) either induction CHT or induction RT-CHT, each followed by surgery, with definitive RT-CHT (no surgery). Due to the heterogeneity of patient, tumor and treatment characteristics across these trials, various meta-analyses (MAs) have been performed to define the optimal treatment approach in this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 30 publications
(38 reference statements)
0
9
0
Order By: Relevance
“…Recent data on the use of modern postoperative TRT [22] seem to overcame negative impact of historic data [23,24], since it enabled effectively concentrating on patients harboring high risk features. In Stage IIIA NSCLC, less than a half of the institutions would still consider surgical multimodality approach likely due to a number of group/society guidelines and recommendations [25,26] in spite of the fact that serious criticism and a number of aws and fallacies have been highlighted in recent years [27][28][29][30]. In, inoperable cases, the vast majority of departments would prefer concurrent RT-CHT, following highest level of evidence existing for more than a decade [31][32][33].…”
Section: Discussionmentioning
confidence: 99%
“…Recent data on the use of modern postoperative TRT [22] seem to overcame negative impact of historic data [23,24], since it enabled effectively concentrating on patients harboring high risk features. In Stage IIIA NSCLC, less than a half of the institutions would still consider surgical multimodality approach likely due to a number of group/society guidelines and recommendations [25,26] in spite of the fact that serious criticism and a number of aws and fallacies have been highlighted in recent years [27][28][29][30]. In, inoperable cases, the vast majority of departments would prefer concurrent RT-CHT, following highest level of evidence existing for more than a decade [31][32][33].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, two phase II trials comparing chemotherapy plus surgery to surgery alone found a similar significant improvement in median survival with chemotherapy [11,12]. In the last years, clinicians' attention has shifted to the role of surgery following neoadjuvant therapy, since no published study has established the superiority of this approach over dCR, yet and the main concern is the potential for increase surgical morbidity and mortality [13]. Definitive concurrent CR is the standard treatment, as shown in a metanalysis by Auperin et al [14]; by comparing six randomized trials about outcomes of concomitant over sequential dCR in patients with locally advanced NSCLC, concomitant combination increases 3-years overall survival (OS) of a 5.7% and 5-years OS of a 4.5%.…”
Section: Local Control: Surgery or Radiotherapy?mentioning
confidence: 99%
“…There was no difference in 5-year OS (40% vs. 44%, p = 0.34) or PFS (35% or 32, p = 0.75) between the CHRT and surgical arms, respectively [39]. Results of these studies were the subject of four meta-analyses/systematic reviews [31,[40][41][42] which were summarized by Jeremic et al [43] who clearly showed that there is no place for surgery in a multimodality treatment in these patients. The most recent meta-analysis of Pottgen et al also analyzed randomized trials comparing surgery with definitive RT as local curative treatment options within the framework of different multimodality treatments for patients with locally advanced (LA-NSCLC).…”
Section: Neoadjuvant Cht Followed By Crt Vs Surgerymentioning
confidence: 99%